Immigrant Indian Professional's experiences in the Australian Workplace - Gowan, Sunaina; Teal, G. (IACSIT Press, 2015)
This qualitative study aims to explore the process underlying perceived discrimination in the workplace. Based on twenty in-depth interviews with Indian immigrants who are professionals or managers, we argue that due to tougher legislation against discrimination in the workplace, discrimination continues to exist in Australian organisations, but in subtle forms. These include ridicule, withholding information, social isolation, passing remarks and making unfair accusations, each causing ethnic minority professional’s stress. The research also provides evidence that there is devaluation of skilled immigrants in Australia, at a time when the country is in competition with other migration nations for scarce and in-demand human capital. With the increasing diversity in the work environment, Australian organisations need to make proper adjustments regarding workers’ interests and needs, and to make sure the work environment is equitable and inclusive.